Drought tolerance classification of common oilseed species using seed germination assay (Journal of Oilseed Brassica, 2026)
Drought stress delays the onset of germination, reduces germination rate and percentage and reduces normal seedling emergence which may limit plant growth and crop yield.This study quantified the germination responses of 10 industrial and edible oilseed crops (Brassica alba, B. carinata, B. juncea, B. napus, B. rapa, Camelina sativa, Crambe abyssincia, Thlaspi arvense, Arachis hypogea and Glycine max) at different levels of osmotic potential (OP) to determine the effect of OP on germination time course, maximum seed germination (MSG), time to 50% seed germination (T50), and germination rate (GR). Maximum germination varied with different levels of OP. MSG and GR decreased with decreasing OP and the time required for the onset of germination increased with decreasing OP. Averaged across species, there were 10, 22, 38 and 62 hours delay in onset of germination when OP was gradually decreased from 0 MPa (control) to -0.2 MPa, -0.4 MPa, -0.6 MPa and -0.8 MPa respectively. The time to 50% germination increased across species and germination rate decreased linearly with decreasing OP. The average time to reach 50% of MSG increased 10, 42, 70 and 142 % with decreasing OP and GR decreased by 8, 27, 39 and 58% when OP changed from 0 MPa to -0.2, -0.4.-0.6 and -0.8 MPa respectively. Based on the T50 drought tolerance index and GR index, juncea, carinata and pennycress were more drought tolerant, canola and rapa were considered as intermediate drought tolerant and other species (soybean, peanut, alba, camelina and crambe) were drought susceptible. The effect of OP on onset of germination, time to 50% germination, MSG and GR arose from the inhibitory effect of OP reduction on the overall process of germination when OP decreased from 0 MPa.The species-specific functions can be used to model germination under variable moisture stress conditions.